Relationship between dermatoglyphics and blood group of male and female first-year medical students at Rama Medical College, Kanpur - Hamid Ansari; Mohammad Faizan Ansari; Medha Das (Asian Journal of Medical Sciences, 2023)
Background: Apart from the flexion crease and secondary folds, dermatoglyphics is the scientific study of naturally existing epidermal ridges and their arrangement on the digits, palms, and soles. In medicolegal cases, fingerprints can be used to identify suspects, victims, and other people who touch a surface as well as to diagnose inherited diseases. ABO blood group is divided into A, B, AB, and O. ABO type is determined by two antigens and two antibodies. Due to the presence or absence of the D antigen, it is further divided into Rh-positive and Rh-negative. Aims and Objectives: This study aimed to find correlation between ABO and Rh blood group with dermatoglyphic pattern in human beings. Materials and Methods: The study was conducted among 107 medical students studying at RMCHRC, Kanpur, UP, India. Rubber stamp ink pads were utilized to smear each finger. Imprints were obtained, and each fingerprint pattern was inspected and documented using a strong hand lens on a sturdy white piece of paper. Results: Among 1070 fingerprint patterns studied, the most common pattern observed was whorl. This pattern was present in 226 male’s digits (49.23%) and 233 female’s digits (50.26%), totaling to 459 forming 42.89% of the total patterns observed. B + blood group was the most common blood group present with whorl pattern, seen in 92 males and 99 females. Conclusion: This study shows the association between the distribution of dermatoglyphics, ABO, Rh blood group, and gender.